2017
DOI: 10.7555/jbr.31.20170031
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation and sulfation of sex steroid hormones in inflammatory liver

Abstract: Sex steroids, also known as gonadal steroids, are oxidized with hydroxylation by cytochrome P450, glucuronidation by UDP-glucuronosyltransferase, sulfation by sulfotransferase, andO-methylation by catechol O-methyltransferase. Thus, it is important to determine the process by which inflammation influences metabolism of gonadal hormones. Therefore, we investigated the mechanism of metabolic enzymes against high physiologic inflammatory responsein vivo to study their biochemical properties in liver diseases. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…CYP17A1 converts progesterone to androstenedione, which is a direct precursor of testosterone biosynthesis 40 . CYP19A1 converts testosterone to oestradiol and hydroxylation of oestradiol by CYP1B1 to produce 4-OH-oestradiol and 2-OH-oestradiol 41 . CYP1B1 can further convert 4-OH-oestradiol and 2-OH-oestradiol into quinone and semiquinone, which can produce ROS through redox cycle, resulting in oxidative damage 42 .…”
Section: Discussionmentioning
confidence: 99%
“…CYP17A1 converts progesterone to androstenedione, which is a direct precursor of testosterone biosynthesis 40 . CYP19A1 converts testosterone to oestradiol and hydroxylation of oestradiol by CYP1B1 to produce 4-OH-oestradiol and 2-OH-oestradiol 41 . CYP1B1 can further convert 4-OH-oestradiol and 2-OH-oestradiol into quinone and semiquinone, which can produce ROS through redox cycle, resulting in oxidative damage 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The liver is involved in metabolism of a number of hormones, therefore its disease may be accompanied by further hormonal disorders (Tomych, 2015). In particular, inflammatory processes in the liver affect metabolism of sex steroids, and may also suppress their binding with receptors throughout the whole body (Lee et al, 2017). Research has shown the complex relation of sex hormones with the liver, because it plays a role of mediator in a number of systemic effects on human and animal organisms (Klimyuk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%